Modeling and analysis of energy losses under transient conditions in induction motors - Ali Dalabeeh; Ashraf Samarah; Abdallah Ershoud Alzyoud; Ayman Y. Al-Rawashdeh; Khalaf Y. Alzyoud (International Journal of Electrical and Computer Engineering (IJECE), 2022)
The present study is mainly concerned with solving the problems associated with energy losses resulting from starting transient conditions. In the present study, the possibilities of decreasing starting transient condition energy losses are investigated. Additionally, a comparison of the energy losses using different starting methods is also conducted. In this work, a complete description for deriving the equations used to calculate energy losses, mathematical analysis of the energy losses, the models of the different methods in this work were simulated using MATLAB/Simulink; and the results of energy losses and the dynamic characteristics are provided. Simulation results showed that the minimum starting energy losses were accomplished by soft starting method, in which the starting current could be reduced to the minimum value.